2009
DOI: 10.1007/s00253-009-1918-7
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high-yield rapamycin-producing strains through protoplasts-related techniques

Abstract: Rapamycin is a 31-member ring macrolide produced by Streptomyces hygroscopicus and has many applications in clinical medicine. In the present work, several protoplasts-related techniques including protoplasts mutation, intraspecies and interspecies protoplasts fusion were tried to improve the rapamycin productivity in S. hygroscopicus. Although mutation and fusion of different protoplasts of S. hygroscopicus did not improve the productivity of rapamycin significantly, the interspecies fusion of protoplasts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Therefore, further improvement of the rapamycin titer and generation of diverse derivatives of rapamycin in S. hygroscopicus has been imperative for its commercial development and clinical applications. 62 In an attempt to improve rapamycin productivity, fermentation medium optimization as described in the previous section, 16,18,53,54 in addition to classical strain improvement, 63 protoplasts-related techniques 64 and high-throughput screening method 65 have been developed. Demain's research group obtained a higher rapamycin-producing mutant from the protoplasts of S. hygroscopicus FC904 mutants treated with 1 mg ml 脌1 of gentamicin, widely used aminoglycosides, where an HPLC analysis showed that the rapamycin titer for this mutant (139 mg l 脌1 ) was 60% higher than that for the parent strain.…”
Section: Mutagenesis and Mutasynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further improvement of the rapamycin titer and generation of diverse derivatives of rapamycin in S. hygroscopicus has been imperative for its commercial development and clinical applications. 62 In an attempt to improve rapamycin productivity, fermentation medium optimization as described in the previous section, 16,18,53,54 in addition to classical strain improvement, 63 protoplasts-related techniques 64 and high-throughput screening method 65 have been developed. Demain's research group obtained a higher rapamycin-producing mutant from the protoplasts of S. hygroscopicus FC904 mutants treated with 1 mg ml 脌1 of gentamicin, widely used aminoglycosides, where an HPLC analysis showed that the rapamycin titer for this mutant (139 mg l 脌1 ) was 60% higher than that for the parent strain.…”
Section: Mutagenesis and Mutasynthesismentioning
confidence: 99%
“…However, the combination of interspecies protoplasts fusion and one round of genome shuffling generated a high-yield rapamycin producer with an outstanding yield of 445 mg l 脌1 . 64 Furthermore, as a result of the protoplast-related mutation and fusion experiments, it was observed that nearly all the highyield rapamycin-producing strains shared a similar phenotype: round colonies with wrinkled edges and abundant yellow aerial mycelia.…”
Section: Mutagenesis and Mutasynthesismentioning
confidence: 99%
“…With the widespread clinical application and promising prospects, rapamycin has recently attracted much attention of many researchers and pharmaceutical companies. So far, considerable efforts have been made to improve rapamycin production, such as fermentation technology optimization [7,26,27], traditional strains mutation [8,46,50], and protoplast-related techniques [5]. Notably, ultraviolet mutagenesis, as a traditional method, has been successfully applied in the field of microbial breeding.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, mutagenesis and protoplast fusion have been combined for whole genome shuffling to improve the production of antibiotics [22,72,75]. In addition, a number of molecular engineering strategies, often focused on optimizing precursor levels or expression of rate-limiting enzymes involved in secondary metabolite biosynthesis, have been summarized in other reviews [3][4][5][6]51].…”
Section: Introductionmentioning
confidence: 99%